Atypical deletion of Williams-Beuren syndrome reveals the mechanism of neurodevelopmental disorders - Jianrong Zhou; Ying Zheng; Guiying Liang; Xiaoli Xu; Jian Liu; Shaoxian Chen; Tongkai Ge; Pengju Wen; Yong Zhang; Xiaoqing Liu; Jian Zhuang; Yueheng Wu; et al. (BMC, 2022)
Abstract Genes associated with specific neurocognitive phenotypes in Williams-Beuren syndrome are still controversially discussed. This study identified nine patients with atypical deletions out of 111 patients with Williams-Beuren syndrome; these deletions included seven smaller deletions and two larger deletions. One patient had normal neurodevelopment with a deletion of genes on the distal side of the Williams-Beuren syndrome chromosomal region, including GTF2I and GTF2IRD1. However, another patient retained these genes but showed neurodevelopmental abnormalities. By comparing the genotypes and phenotypes of patients with typical and atypical deletions and previous reports in the literature, we hypothesize that the BAZ1B, FZD9, and STX1A genes may play an important role in the neurodevelopment of patients with WBS.